Compensation of the temperature instability of the quartz generator of the intelligent electronic device for measuring electric parameters - P. Zvada (Вестник Северо-Кавказского федерального университета)
The purpose of the article is to study the possibility of compensating for the temperature instability of the quartz oscillator of an intelligent electronic device in case of loss of a synchronizing signal from a navigation satellite.An algorithm for software compensation of the temperature instability of a quartz oscillator has been developed and implemented. The author's implementation of temperature compensation of quartz oscillators is implemented as a program in the LabView FPGA environment, tested in a series of experiments using two CompactRIO controllers: a reference one and a device with software compensation. As a result of applying compensation, it was possible to linearize the dependence and reduce it from 0,65 cycles per degree Celsius to 0.04 cycles per degree Celsius for a 200 MHz generator. This compensation method does not require material costs or changes in the design of the measuring device and is ready for use in most measuring devices